THE EXPERIENCES OF FLIGHT AND THE RISK IN THE SPEECHES OF PRACTIONERS OF FREE FLIGHT (Fiep Bulletin - online, 2013)
Given this variability offered by the flight, the uncertainty afforded by the unpredictability of the aerial environment, the daring to challenge the space as flying birds, we sought to investigate with this study the senses of risk as a generator of communion among the practitioners of free flight. In order to get nearer the reality of the universe of practitioners of this sport, we conducted an exploratory research, with a qualitative approach, where issues related to the risk-adventure of flying were approached as the main theme. We analyzed the risk and the influence of sensations deriving from this risk in the process of cohesion of different communities. We analyzed yet the testimonies of a mailing list from Internet published in the book Parapente Brasil (2002) and interviews published in the magazines Air and Air Time Adventure, specialized in free flight. The interpretation of these speeches was made by the method of content analysis used by Bardin (2004). The speeches of flyers, present in this study, point to a constant preoccupation with issues related to risk, safety, adventure and pleasure. Issues which are also related to the choice of modality with the level of performance that the practitioner wants to achieve and with the way by which the different communities are formed within the free flight. The risk in this context emphasizes the sense of social cohesion so that those who face the same risk feel similar. We can consider that the similarity in the experience of the risk is an element generator of communion among the actors in the practice of this sport, as noted Almeida (2008) in his studies. In free flight the actors are able to alter their daily routines, to explore their own limits and transmit sense to the action of flying.
Keywords: free flight; risk